Right Atrium Primary Cardiac Lymphoma Causing Heart Failure - Doño, Angel; Lounsbury, Cassidy; Garrett, Harvey Edward, Jr (The Thoracic and Cardiovascular Surgeon Reports, 2024)
Background Patients with primary cardiac tumors may present with symptoms based on the size and location of the tumor. Symptoms may include congestive heart failure secondary to intracardiac obstruction, systemic embolization, arrhythmias, and constitutional symptoms.Case Description A patient presented with new onset atrial fibrillation and heart failure. Workup including open surgery revealed a primary cardiac lymphoma.Conclusion Cardiac tumors present with a variety of symptoms and are best evaluated by echocardiogram, computed tomography angiography, and magnetic resonance imaging. Tissue diagnosis is necessary. Although primary cardiac lymphoma is rare, long-term survival after chemotherapy and rituximab is superior to other cardiac malignancies.
Keywords: cardiac; heart failure; imaging (all modalities); off-pump surgery; positron emission tomography; tumor